Effects of cigarette smoking on hematological parameters in male smokers in Al-Bayda city, Libya - Al Salhen, Khaled S.; Abdalslam, Rhab D. (Al-Mukhtar Journal of Sciences, 2014)
Tobacco smoking use is widely spread throughout the world. Tobacco smoking has been claimed to cause a wide variety of health problems such as atherosclerosis, mutagenesis of exposed cells and cancer. The effects of smoking on human health are serious and in many cases, deadly. The present study was done to investigate the effect of cigarette smoking on some hematological parameters in male smokers. The study is carried out on thirty Libyan male smokers, who smoked at least 10 cigarettes per day for at least15 years. Their age ranged between 30-60 years. Control (non-smokers) group was collected with the same range of age for statistical comparison. The results of the study revealed a significant increase of hematological parameters (Hb: Hemoglobin; PCV: Packed cells volume; RBC: Red blood cell and WBC: White blood cell) in smoker group when compared with the control. No significant difference of the platelet count was recorded in smoker group when compared with control. Furthermore the level of malondialdehyde (MDA), which is an indicator of lipid peroxidation and oxidative stress significantly increased in cigarette smokers group when compared with control group. To conclude, cigarette smoking leads to oxidative stress by free radical generation (Reactive oxygen species-ROS) by the mechanism of lipid peroxidation. Smoking exerts negative influence on the hematological parameters and these are the contributing factors that lead to cardiovascular and atherosclerosis that usually occur in cigarette smokers and cause of death.